An analysis of Accelerated Christian Curriculum in Biblical Christian Worldview - Liana, Linda (Universitas Pelita Harapan, 2020)
God gave man his commission (Gen. 1:26-30), called the Cultural Mandate. In this mandate mankind is to steward the created order, in accordance with Godâ€™s law-Word, for Godâ€™s glory. Shortly before the resurrected Lord Jesus Christ ascended to heaven, he issued the Great Commission (Matt. 28:18-20). The Great Commission command to disciple all the nations into obedience to the comprehensive and absolute lordship of Jesus Christ. There is no area of thought, life, or culture outside the scope of the Creation/ Dominion Mandate or the Great Commission. Thus, the extent of the Creation Mandate and the extent of the Great Commission necessitate Christian Education. Accelerated Christian Curriculum is a curriculum that has been helping pastors and parents by developing and publishing quality, character building Christian educational materials for Grade Levels K3-12. By integrating character building principles and scripture memory into the academics, the program helps children master each concept before moving to the next concept. In this essay I analyze the Accelerated Christian Education curriculum from a Biblical Christian Worldview.Â